Peningkatan Harga Diri pada Remaja dengan Tuberkulosis Kelenjar melalui Terapi Ners Generalis (Journal of Telenursing (JOTING), 2023)
This study aimed to provide generalist nurse intervention to adolescent clients with situational low self-esteem. The method used was a case study approach with one respondent, carried out for two days on 1-2 April 2021. The results obtained were that generalist therapy was proven to increase adolescent self-esteem. Generalist therapy has proven effective with specialist nursing therapy, including supportive therapy and family psychoeducation. Keywords: Situational low self-esteem, Adolescents, Glandular TB, Generalist Nurse Therapy